Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. The impact of strategic leadership on improving employee performance at King Fahd Central Hospital in Jazan "An applied study on employees at King Fahd Central Hospital in Jazan"Mr. Jebreel Abdu Mohajer2. The Role of Practicing Strategic Entrepreneurship in transformation Towards Smart Organizations "A Field Study on Palestinian Information Technology Companies"Mr. Nedal Farouq Abu Ghaben, Mr. Ibrahem Subhi Bakri, Asst-Prof. Ahmed Farouq Abu Ghaben3. The impact of digital marketing on the pilgrim’s experience: A field studyMr. Basim Saud Alhazmi, Dr. Masher Hani Baishin, Ms. Dana Monzer Rajkhan4. The role of electronic management in developing the work environment in public sector institutions in Asir regionMs. Asma Ali Alyausi, Co-Prof. Mohammed Alsagheer Qasem Alshaebi5. Assessing the Influence of Corporate Governance Principles on Disclosure and Financial Report Quality: Evidence from Saudi Listed CompaniesAsst-Prof. Hanan Rashid Albalwy6. The Impact of Strategic Cost Management Methods on Supporting the Continuity of Food Manufacturing Companies (A study on a sample of food manufacturing companies in Khartoum State)Co-Prof. Mohammed Ishag  Abdalla7. The extent of knowledge and awareness of Saudi university students about green finance: An exploratory study of a sample of female students at Taif universityDr. Razaz Houssien Felimban8. The Impact of Training and Professional Development on Enhancing Efficiency, Growth,  and Sustainability of Family Businesses in the Kingdom of Saudi ArabiaDr. Hanan Abdullah Natheer
Keywords: Journal of Economic, Administrative and Legal Sciences